Genetic relationship of baculovirus infected common pests on vegetables in the Southern of Vietnam accessed by lef-8 gene - Phuong Thao, Nguyen Thi; Long, Le Thanh; Hanh, Van Thi; Hong Van, Nguyen Thi; Duy, Nguyen Khac (Academia Journal of Biology, 2013)
Polymerase chain reaction was applied to amplify baculovirus-specific lef-8 gene. Lef-8 gene sequences were used to access genetic distances and phylogenetic relationship of baculovirus derived from Southern Vietnam and other baculovirus from Genbank. The results showed that almost baculovirus from Southern Vietnam expressed 450bp of lef-8 gene. The genetic distance between baculovirus from Southern Vietnam and Alpha-2 baculovirus was lowest (0.346±0.069), suggesting that they had close genetic relationship. Neighbor-joining method was applied for phylogenetic construction. Bootstrap analyses (using 1000 replications) were used to access the confidence in branching order. Phylogenetic tree demonstrated that baculovirus from Southern Vietnam and Alpha-2 baculovirus, especially spodoptera_litura_NPV, located in the same clade with 86% bootstrap value, suggesting that spodoptera_litura_NPV has wide distribution in Southern Vietnam.